EN MAGER HELGENINDES MAGT: Kvindelig mystik i middelalderen og feministiske genfortolkninger - Asher, Judith (Tidsskriftet Antropologi, 1998)
Judith Asher: The Power of a Skinny Saint: Fasting Practices of Medieval Female Mystics and Feminist Rereadings In connection to the current Western ideal of a thin and disciplined female body, historical 252 evidence has been sought of eating disorders among women prior to medical diagnoses of anorexia nervosa and bulimia. One of the first well-documented instances of such food-related body denial in Western history is European medieval women saints, who in the standard church hagiography have been revered for the “miracle” of surviving on a negligible intake of food, inedia miraculosa. This relatively marginal phenomenon has come to receive surprisingly broad attention; the “holy anorexics” are now a standard reference both in feminist scholarship and in popular women’s literature. Contemporary feminist interpretations of these saints tend to encounter a fundamental ambiguity: whether to pronounce the women mystics victims of oppression or agents of liberation. This article describes the self-imposed starvation regime of medieval mystics with reference to the idioms of eating and feeding that informed their socio-historical context. It then goes on to outline the interpretive ambiguity current among feminist rereadings and propose that this uncertainty points to the inherently contradictory nature of broad-based social gender definitions.